COMPARATIVE ANALYSIS ON DETERMINING HORIZONTAL WELL PRODUCTIVITY IN LOW QUALITY RESERVOIR AT BEKASAP AREA - AGUNG HENDRA SUCITRA (NIM : 22207317), ANAK
Horizontal well have been successfully applied to enhance production from low quality formation. Horizontal wells can provide significant improvement of production over vertrical wells. However, success in applying the technology requires carefull consideration of a number of factor. Pressure Transient Analysis (PTA) has been proven as a reliable method to investigate formation damage in a well. Unfortunately, this method has difficulty to apply and costly if this method applied on all horizontal well. Quicker look, cheaper and more reliable method must be defined to predict well formation damage. Flow Efficiency (FE), which is has an adequate reservoir data, is a method that can be used to predict well formation damage in a quick look. This research take horizontal well with low quality because the number of well is increasing and there is lack knowledge on horizontal well performance and its expensive so its need justification too before work over can be done on horizontal wells. ...